BENTUK PENYELESAIAN HUKUM WANPRESTASI PADA PERJANJIAN PINJAM MEMINJAM SECARA ONLINE (Solusi, 2022)
If there is a dispute or default in the implementation of an online-based lending and borrowing agreement, the legal settlement is based on Article 29 letter e of POJK Number 77/POJK.01/2016 that dispute resolution between the parties can take 2 (two) ways, namely through litigation and non-dispute. -litigation. If the parties choose to resolve the dispute through litigation, then a civil lawsuit is filed to the court concerned, but if the parties choose through non-litigation then the parties can resolve it through mediation, negotiation, or arbitration according to Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution.